2010
DOI: 10.1021/cm1007284
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Solution Deposition of Ceria Textured Thin Films from Novel Mixed-Ligand Metal−Organic Precursors

Abstract: Novel solution precursors for CeO 2 buffer layers, based on mixed-ligand hydroxocomplexes of lanthanide acetates and nitrates with monoethanolamine (MEA) and diglyme, acting as both ligands and solvents, have been developed. The formation of mixed-ligand Ce(IV) complexes in both liquid and transparent gel precursors have been confirmed by electrospray ionization-mass spectroscopy (ESI-MS) and 1 H nuclear magnetic resonance (NMR) spectroscopy. The features of thermal decomposition of gel precursor samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Additional interest in systems of REE carboxylates with amines is also caused by their application as precursors in the solution method for the preparation of inorganic thin-film materials based on REE: oxides and fluorides [7][8][9][10]. An important advantage of these systems is a slight hydrolysis under the action of amines to form an amorphous gel providing upon annealing the homogeneity and uniformity of the formed film of inorganic material.…”
Section: Introductionmentioning
confidence: 99%
“…Additional interest in systems of REE carboxylates with amines is also caused by their application as precursors in the solution method for the preparation of inorganic thin-film materials based on REE: oxides and fluorides [7][8][9][10]. An important advantage of these systems is a slight hydrolysis under the action of amines to form an amorphous gel providing upon annealing the homogeneity and uniformity of the formed film of inorganic material.…”
Section: Introductionmentioning
confidence: 99%
“…In water the presence MEA acts as strong alkali like NH 3 ⋅ aq and can hydrolyze lanthanides. So, we have found that in MeCN either Ce(Acet) 3 ⋅xHAcet (HAcet = acetic acid) or mixture of Ce(NO 3 ) 3 ·6H 2 O and HAcet (1:3 molar ratio) reacted with MEA forming mixed ligand hydroxocomplexes of Ce(IV) that was confirmed by IR and 1 H NMR, electrospray MS and elemental analysis [16]. Crystals of mixed ligand compound I grown as by-product of analogous hydroxocompounds were synthesized by means of Ce(NO 3 ) 3 ·6H 2 O addition to a mixture of HPiv and MEA (3:5) in MeCN [17].…”
mentioning
confidence: 67%
“…In more-polar solvents, the coexistence of both isomers was observed while the E:Z ratio increased with increasing polarity, reaching the maximum ratio of 63:37 in DMSO−d 6 solution. The ligands were comprehensively characterized by 13 C and 19 F NMR one-dimensional (1D) and two-dimensional (2D) experiments; the full data set and assignments are given in the Experimental Section.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9 For the preparation of ceria thin films, several physical and chemical synthetic methods have been applied, for example, gas-phase methods such as pulsed laser deposition (PLD), 10,11 metal-organic chemical vapor deposition (MOCVD), 12,13 atomic layer deposition (ALD), 14−17 or solution-based methods. 18,19 In this context, chemical vapor deposition (CVD) is a versatile coating technique, which offers decisive advantages including conformal step coverage, large deposition area, and better controllability over material properties and composition. Use of plasma-enhanced deposition (PECVD) allows film preparation under nonequilibrium conditions, usually at low temperatures, which results in film characteristics that are not obtainable by other deposition techniques.…”
Section: ■ Introductionmentioning
confidence: 99%